1996
DOI: 10.1037/0022-0663.88.1.110
|View full text |Cite
|
Sign up to set email alerts
|

Using causal persuasive arguments to change beliefs and teach new information: The mediating role of explanation availability and evaluation bias in the acceptance of knowledge.

Abstract: In this article processes by which causal arguments effect change in established beliefs were explored. The hypothesis that explanation availability mediates belief change in response to causal arguments was tested in 2 experiments. Persuasive communications used causal evidence, noncausal (statistical) evidence, or both to argue that AIDS is not transmissible by casual contact. Results supported the authors' hypothesis. Causal arguments produced the greatest belief change, with the effect mediated by explanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 47 publications
2
49
0
Order By: Relevance
“…Initial research on causal arguments demonstrated a main effect: causal arguments can be more effective than non-causal arguments for changing beliefs (Slusher & Anderson, 1996). Together, recent research (Tobin & Weary, 2008) and the current findings demonstrate the existence of two sets of moderating variables: (1) personal levels of causal uncertainty and causal importance, and (2) the source's level of perceived causal and content-area expertise.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Initial research on causal arguments demonstrated a main effect: causal arguments can be more effective than non-causal arguments for changing beliefs (Slusher & Anderson, 1996). Together, recent research (Tobin & Weary, 2008) and the current findings demonstrate the existence of two sets of moderating variables: (1) personal levels of causal uncertainty and causal importance, and (2) the source's level of perceived causal and content-area expertise.…”
Section: Discussionmentioning
confidence: 65%
“…For the non-causal arguments, instead of explaining why the negative consequences would occur, we provided statistical information that suggested that the effects would occur (Slusher & Anderson, 1996;Tobin & Weary, 2008). For example, to support the idea that stress levels would increase, we stated that "studies have found that vacations longer than 5 to 7 days increased post-vacation stress among students by up to 16%."…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent studies have investigated biased assimilation in domains such as AIDS prevention education (Slusher & Anderson, 1996), assessing the guilt of acused rape perpetrators (Weiner, Weiner, & Grisso, 1989), and the possibility of technological accidents (Plous, 1991). Miller, McHockey, Bane, and Dowd (1993) critiqued the original Lord et al (1979) study by demonstrating that the attitude polarization effect is limited to certain types of attitude assessment.…”
Section: Biased Assimilation Of Biological Argumentsmentioning
confidence: 99%